Confined impinging jet reactor for high-throughput continuous flow mononitration of salicylic acid - Khan, Muzammilanwar S.; Shaikh, Tabrez R.; Kulkarni, Sphurti P.; Patil, Abhishek A.; Kulkarni, Amol A. (Organic Process Research & Development, 2025)
Novel approach is reported for highly efficient continuous mononitration of salicylic acid using confined impinging jet reactor (CIJR) with a vent. Initially, controlled semibatch reactions are optimized to achieve complete conversion and formation of mononitro products with very high selectivity for 5-nitrosalicylic acid (5-NSA). Further, the combination of computational fluid dynamics simulations and experiments is employed to optimize CIJR design and operating flow conditions, suitable to yield only mononitro products with excellent control over mixing, heat transfer, and liberation of fumes during continuous flow reaction. Detailed analysis of internal flow patterns, rate of heat generation, and concentration distribution inside the CIJR facilitated the optimization of present exothermic reaction in a safe manner. In less than a minute, complete salicylic acid (SA) conversion with good yield and better selectivity for 5-NSA is achieved using the CIJR. Safety and clogging issues are addressed effectively, even at a relatively lower mole ratio (1:5) of SA:acetic acid (AcOH). The present approach is quite scalable using the numbering-up strategy, with advantages viz. nonfouling, high throughput, and the small footprint of CIJR.
Keywords: computational fluid dynamics; confined impinging jet reactor; high-throughput synthesis; salicylic acid nitration